Genealogical Tree of Russian schools on Nonlinear Dynamics - Prants, S. V.; Uleysky, M. Yu. (Discontinuity, Nonlinearity, and Complexity, 2026)
One of the most prominent feature of research in Russia and the former Soviet Union is so-called scientific schools. It is a collaboration of researchers with a common scientific background working, as a rule, together in a specific city or even at an institution. The genealogical tree of scientific schools on nonlinear dynamics in Russia and the former Soviet Union is grown. We use these terminology in a broad sense including theory of dynamical systems and chaos and its applications in nonlinear physics. In most cases we connect two persons if one was an advisor of the Doctoral thesis of another one. It is an analogue of the Candidate of Science thesis in Russia. If the person had no official advisor or we don’t know exactly who was an advisor, we fix that person who was known to be an informal teacher and has influenced on him/her very much.